Tips on how to make hay at a smallholder farm: Part 2 - Manyawu, Godfrey J. (International Livestock Research Institute, 2025)
This is part two of a video that explains how to make and store hay for livestock using readily available forages at a smallholder farm. Haymaking is recommended for all environments where livestock keepers can get excess forage during periods of peak pasture growth. The video was developed as an innovation of CGIAR led by ILRI.